Digitalizing planning culture: A change towards information model-based planning in Finland - Pilvi Nummi; Aija Staffans; Otso Helenius (Journal of Urban Management, 2023)
While digitalization is expected to bring benefits in the area of land use planning, it is also redefining planning practices and entire planning cultures. Limited research exists on this digital transformation, and this article aims to narrow this gap through an empirical case study. In Finland, there is an ongoing transition towards information model (IM)-based planning, driven by public government development programs. Its principal focus is to achieve national-level interoperability of plan data. A harmonized IM for local master and detailed plans has recently been developed for use in municipal urban planning in the future. In addition, a national information system (IS) for built environment data is currently being developed. In this article, the perspectives of Finnish urban planners towards the national IM and IM-based planning were examined through a questionnaire. The results indicate that IM-based planning has a strong impact not only on planning outcomes (i.e., land use plans) but also on the planning context (e.g., planning practices and the planners themselves, software and information systems (ISs), and planning law). We argue that the high expectations set for IM-based planning will not be met without paying attention to the viewpoints of planners, planning practices, and the changes to planning culture in a wider sense. In addition to the technological aspects, the focus should also be on the social and contextual elements of planning.
Keywords: 710; Digital transformation; IM; Information model; Interoperability; Plan data; Planning culture; Urban planning